Chromatin Regulators Ahc1p and Eaf3p Positively Influence Nitrogen Metabolism in Saccharomyces cerevisiae - Chen, Yu; Zeng, Weizhu; Ma, Wenjian; Ma, Wei; Zhou, Jingwen (Frontiers in Microbiology, 2022)
There is a complex regulatory network of nitrogen metabolism in Saccharomyces cerevisiae, and many details of this regulatory network have not been revealed. This study explored the global regulation of nitrogen metabolism in S. cerevisiae from an epigenetic perspective. Comparative transcriptome analysis of S. cerevisiae S288C treated with 30 nitrogen sources identified nine chromatin regulators (CRs) that responded significantly to different nitrogen sources. Functional analysis showed that among the CRs identified, Ahc1p and Eaf3p promoted the utilization of non-preferred nitrogen sources through global regulation of nitrogen metabolism. Ahc1p regulated nitrogen metabolism through amino acid transport, nitrogen catabolism repression (NCR) and the Ssy1p-Ptr3p-Ssy5p signaling sensor system. Eaf3p regulated nitrogen metabolism via amino acid transport and NCR. The regulatory mechanisms of the effects of Ahc1p and Eaf3p on nitrogen metabolism depended on the function of their histone acetyltransferase complex ADA and NuA4. These epigenetic findings provided new insights for a deeper understanding of the nitrogen metabolism regulatory network in S. cerevisiae.